Comparison of Changes in Corneal Biomechanical Properties after Photorefractive Keratectomy and Small Incision Lenticule Extraction - Yusuf Yıldırım; Onur Ölçücü; Ali Demircan (Türk Oftalmoloji Dergisi, 2016)
Objectives: To compare the postoperative biomechanical properties of the cornea after photorefractive keratectomy (PRK) and small incision lenticule extraction (SMILE) in eyes with low and moderate myopia. Materials and Methods: We retrospectively examined 42 eyes of 23 patients undergoing PRK and 42 eyes of 22 patients undergoing SMILE for the correction of low and moderate myopia. Corneal hysteresis (CH) and corneal resistance factor (CRF) were measured with an Ocular Response Analyzer before and 6 months after surgery. We also investigated the relationship between these biomechanical changes and the amount of myopic correction. Results: In the PRK group, CH was 10.4±1.3 mmHg preoperatively and significantly decreased to 8.5±1.3 mmHg postoperatively. In the SMILE group, CH was 10.9±1.7 mmHg preoperatively and decreased to 8.4±1.5 mmHg postoperatively. CRF was significantly decreased from 10.8±1.1 mmHg to 7.4±1.5 mmHg in the PRK group whereas it was decreased from 11.1±1.5 mmHg to 7.9±1.6 mmHg in the SMILE group postoperatively. There was a significant correlation between the amount of myopic correction and changes in biomechanical properties after PRK (r=-0.29, p=0.045 for CH; r=-0.07, p=0.05 for CRF) and SMILE (r=-0.25, p=0.048 for CH; r=-0.37, p=0.011 for CRF). Conclusion: Both PRK and SMILE can affect the biomechanical strength of the cornea. SMILE resulted in larger biomechanical changes than PRK